The theory of the impossibility of socialism of Father Juan de Mariana (Journal of the Sociology and Theory of Religion, 2025)
:  In this article, we seek to contextualize the contribution of Father Juan de Mariana to the theory of the impossibility of socialism. After a brief explanation of this theory, we will try to analyze Father Mariana's background through his critical work on the evils of the Society of Jesus. We will have the opportunity to observe how Father Mariana anticipated many of the conclusions reached by the economists of the Austrian School three centuries later, both in relation to the difficulties encountered by the planner and in the consequences of a centralized order.
Keywords: : History of the Economic Thought; Methodology; Preclassical Economic Thought; Austrian School; School of Salamanca.